Investigation of neglected protists Blastocystis sp. and Dientamoeba fragilis in immunocompetent and immunodeficient diarrheal patients using both conventional and molecular methods. - Fakhriddin Sarzhanov; Funda Dogruman-Al; Monica Santin; Jenny G Maloney; Ayse Semra Gureser; Djursun Karasartova; Aysegul Taylan-Ozkan (Public Library of Science (PLoS), 2021)
Introduction The clinical significance of Blastocystis sp. and Dientamoeba fragilis in patients with gastrointestinal symptoms is a controversial issue. Since the pathogenicity of these protists has not been fully elucidated, testing for these organisms is not routinely pursued by most laboratories and clinicians. Thus, the prevalence of these organisms and the subtypes of Blastocystis sp. in human patients in Turkey are not well characterized. This study aimed to determine the prevalence of Blastocystis sp. and D. fragilis in the diarrheic stool samples of immunodeficient and immunocompetent patients using conventional and molecular methods and to identify Blastocystis sp. subtypes using next generation sequencing. Material and methods Individual stool specimens were collected from 245 immunodeficient and 193 immunocompetent diarrheic patients between March 2017 and December 2019 at the Gazi University Training and Research Hospital in Ankara, Turkey. Samples were screened for Blastocystis sp. and D. fragilis by conventional and molecular methods. Molecular detection of both protists was achieved by separate qPCRs targeting a partial fragment of the SSU rRNA gene. Next generation sequencing was used to identify Blastocystis sp. subtypes. Results The prevalence of Blastocystis sp. and D. fragilis was 16.7% and 11.9%, respectively as measured by qPCR. The prevalence of Blastocystis sp. and D. fragilis was lower in immunodeficient patients (12.7% and 10.6%, respectively) compared to immunocompetent patients (21.8% and 13.5%, respectively). Five Blastocystis sp. subtypes were identified and the following subtype distribution was observed: ST3 54.4% (n = 37), ST2 16.2% (n = 11), ST1 4.4% (n = 3), ST6 2.9% (n = 2), ST4 1.5% (n = 1), ST2/ST3 11.8% (n = 8) and ST1/ST3 8.8% (n = 6). There was no statistically significant difference in the distribution of Blastocystis sp. subtypes between immunocompetent and immunodeficient patients. Conclusion and recommendation Our findings demonstrated that Blastocystis sp. and D. fragilis are commonly present in immunocompetent and immunodeficient patients with diarrhea. This study is the first to use next generation sequencing to address the presence of Blastocystis sp. mixed subtypes and intra-subtype variability in clinical samples in Turkey.